"I came, I saw, I conquered": reflections on participating in a PhotoVoice project. Issue 4 (7th June 2021) - Barry, Jennifer; Monahan, Christine; Ferguson, Sharon; Lee, Kelley; Kelly, Ruth; Monahan, Mark; Murphy, Rebecca; Gibbons, Patrick; Higgins, Agnes
Abstract : Purpose: The purpose of this paper is to provide first-hand reflective narratives from participants of their involvement in the overall process, with particular reference to the benefits and challenges of engagement. Design/methodology/approach: Five participants agreed to write a reflective piece of approximately 500 words on their involvement in the PhotoVoice project. Findings: The reflective narratives in this paper demonstrate the personal and professional benefits of sustained and meaningful engagement, while challenges such as power imbalances, identity management, time and cost commitments are discussed. Practical implications: PhotoVoice is a methodology that has the potential to democratise knowledge production and dissemination. Originality/value: There are scant examples in the PhotoVoice literature of the inclusion of participants involvement in dissemination activities. The reflective narratives in this paper demonstrate the personal and professional benefits of sustained and meaningful engagement, while challenges such as power imbalances, identity management, time and cost commitments are discussed.